The Effect of Think Pair Share Model By Mask Media For Students Self Confidence - Ahmad Saifullah; Rasidi Rasidi; Aditia Eska Wardana (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of think pair share model by mask media forstudents self confidence on grade IV Students of Joho Primary School TemanggungRegency.This research method is Pre-Experimental Design with One Group Pretest and PosttestDesign model. The subject were chosen by nonprobability saturation sampling. Sampletaken as many as 26 students. Method of Data completion is done by using selfconfidence questionnaire and self confidence observation. Test the validity ofquestionnaire self confidence instrument by using the formula product moment, andreliability test using cronbach alpha formula by IBM SPSS for Windows version 26.00.analysis prerequisite test consists of normality test. Then proceed with hypothesistesting. Data analysis using non parametric statistic technique that is wilcoxon test byIBM SPSS for Windows version 26.00. The number of items in this questionnaire consistsof 50 questions, while the observation instrument consists of 20 questions. The results ofthe validation of the questionnaire items from 50 test subjects with a value of 0.444 witha significant level of 5% obtained 27 valid questionnaire items, so that the validquestionnaire items can be used as an instrument for collecting item data in the study.While the results of expert validation in the observation instrument are feasible to usewith valid categories.The result of the study show that the Wilcoxon Test analysis with a value of sig. (2-tailed) of 0,000 < 0,05. Based on the results of the analysis and discussion, there is anaverage post-test questionnaire score of 82.42 and an average pre-test questionnaire of72.73. The calculation of the observation assessment in the post-test activity was 70.96and the pre-test activity was 59.03. The result of the study show that the think pairshare model by mask media by mask media has an effect on students self confidence.